Students of State Elementary School 2 Cintaratu Received Health Education on Dengue Fever Prevention (DHF) as an Indicator of a Clean Lifestyle (PHBS) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
DHF can occur at any time of year and affect people of all ages.This disease is linked to  environmental factors and community behavior. Several circumstances can lead to the establishment of DHF in the educational setting. There are two types of factors: internal and external. Internal factors of transmission may include a person's immunity. The conditions of various mosquito breeding places, such as water reservoirs, can be used to determine what causes a person to suffer from  DHF since these factors allow mosquitos to thrive and breed. This is because the water reservoir at SDN 2 Cintaratu appears moist, lacks sunlight, is not cleaned, and is not closed. The purpose is to develop understanding and modify the behavior of public elementary school pupils 2 Cintaratu in  order  to  avoid risk  factors  for  DHF. Lecture,  question  and answer,   discussion,   and   demonstration   are   the   methods employed. The whole audience consisted of 48 students aged 9 to12. In this pre-test question, there are 5 multiple-choice questions with the number of scores on each question is 20 points. This question leads to the student's cognitive dominance to determinethe level of students' knowledge about dengue hemorrhagic feverbefore  being  provided  the  material. Based on the  pretest  and posttest scores, the average number of prestests was 58%, with15 students scoring below average and 33 scoring above average. The  average number  of  posttests was 72%, with  11  students scoring less than the norm, and 37 students scoring more. Conclusion: In achieving the objectives of health promotion carried out, there are four indicators that will be achieved for students from eight PHBS indicators in the school environment, namely, washing hands with clean running water and soap, using clean and healthy toilets, eradicating mosquito larvae, and managing and disposing of waste in its place